2023
DOI: 10.3390/children10111805
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute Sequelae of COVID-19 (PASC) in Pediatrics: Factors That Impact Symptom Severity and Referral to Treatment

Catherine M. Soprano,
Ryan Ngo,
Casey A. Konys
et al.

Abstract: The post-acute sequelae of COVID-19 (PASC) is a complex condition. While there are emerging studies on its effects in adults, there is scarce research regarding the long-term effects of COVID-19 infection among youth. Several researchers have likened long-haul COVID-19 to chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) and postural orthostatic tachycardia syndrome (POTS). In adults, the prognosis for these diagnoses is less promising than that in youth; however, there is currently very little infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…LCS diagnosis has become increasingly difficult as it is characterized by several symptoms, ranging from malaise, fatigue, and muscular fatigue to autonomic dysfunction [8]. Therefore, the most frequent symptoms of LCS mimic chronic fatigue syndrome/myalgic encephalomyelitis and dysautonomia, implying a decrease in daily function and quality of life [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…LCS diagnosis has become increasingly difficult as it is characterized by several symptoms, ranging from malaise, fatigue, and muscular fatigue to autonomic dysfunction [8]. Therefore, the most frequent symptoms of LCS mimic chronic fatigue syndrome/myalgic encephalomyelitis and dysautonomia, implying a decrease in daily function and quality of life [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the risk factors associated with the development of LCS were investigated. Studies on adults identified female sex, severity of initial respiratory disease or overall acute COVID-19 infection, and length of hospitalization for COVID-19 infection as risk factors for CSF [9]. A patient's diet, alcohol use, smoking behaviors, amount of exercise prior to acute COVID-19 infection, and prior sleep patterns may also contribute to the development of LCS [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation